Secondary Emission Effect on SomePre-Equilibrium Nuclear Reactions Spectra at Different Energies - Alattabi, Hadi D.; Shafik, Shafik S.; Kadhim, Masar Abdulzahra (Iraqi Journal of Science, 2019)
The nuclear pre-equilibrium emission spectra have been studied and calculated using the exciton model with different reactions and incident energiesfor the target nuclei: . The secondary emissioncomponent has been inserted to the final emission spectrum and its effectshave been studied for only reactions with primary nucleons emission because the restrictions introduced by primary clusters emission reactions. It revealed a big contributioninenhancing the calculated energy spectra atincident energies more than